Influence of methane content on a LNG heavy-duty engine with high compression ratio. (1st June 2017) - Chen, Zheng; Zhang, Fan; Xu, Boya; Zhang, Quanchang; Liu, Jingping
Abstract: An experiment was conducted to investigate the effects of methane content in natural gas on combustion and performance of a liquefied natural gas (LNG) heavy-duty engine. Two kinds of LNG with different methane contents (i.e. 93% and 99%), in combination with three compression ratios (i.e. CR11.6, CR14 and CR16) and varied spark timings were tested and compared at various engine speeds. The results show that natural gas with 99% methane content has better actual antiknock performance than the one with 93% methane content, and subsequent better power performance and fuel economy. When compression ratio is increased from 11.6 to 14, natural gas with 99% methane content can maintain the maximum loads at all tested speeds, and achieve a maximum decrease of 6.4% in BSFC. On the contrary, the maximum load at high-speed is limited for natural gas with 93% methane content due to knocking combustion. Moreover, natural gas with 99% methane content has larger knock-limited spark advanced angle compared to the one with 93% methane content, so it achieves earlier ignition and then lower BSFC. In conclusion, higher methane content has better comprehensive performance than the lower one in natural gas engines with high compression ratio. Highlights: Compression ratio 11.6, 14 and 16 are studied with two methane contents. Higher methane content can maintain the maximum loads at CR14. Higher methane content achieves a maximum decrease of 6.4% in BSFC. Higher methane content has larger knock-limited spark advanced angle. Higher methane content shows better performance in high CR engine.